Factors Affecting on Immunization Compliance: Iraq - Al-lela, Omer Qutaiba B; Bahari, Mohd Baidi; Baderden, Sara K; Basher, Amina Y; Hamoodi, Hani Kareem (Journal of Pharmacy Practice and Community Medicine)
Objectives: To evaluate immunization status and to identify the family and child demographic factors associated with immunization rate in Iraqi children younger than two years. Method: A cross-sectional and a cluster sampling design were implemented; five hundred twenty-eight representative Iraqi families with children between 18 and 70 months of age were interviewed in five public health clinics in Mosul-Iraq. Demographic characteristics of the child and family, and the child’s immunization history were obtained. Immunization rate or completeness was assessed. Risk factors for partial immunization for the 1-5-3-4-1-1 vaccine series were explored using bivariate analyses and multi-level logistic regression models. Results: Less than half of the children had one missed dose, considered as partial immunization cases. The study found significant associations of immunization completeness with fathers and mother’s education level, mother’s race and family income. Number of preschool children, family income, father’s education, mother’s education and marital status were found that strongly impacted on immunization completeness. Conclusion: There is a need to increase awareness about the benefits and importance of vaccination, as well as the harmful consequences of partial immunization.
Keywords: Immunization Status; Iraqi Child; Complete Immunization; Partial Immunization; Family and Child Factors